Femoral condylar fractures in four continental giant breed rabbits. (21st August 2021) - Dorlis, C.; Garcia‐Pertierra, S.; Richardson, J.; Koterwas, B.; Keeble, E.; Eatwell, K.; Ryan, J.; Clements, D. N.
Abstract : Four male neutered continental giant rabbits aged between 10 and 30 months were presented with femoral condylar fractures, which developed without an observed traumatic injury. Stabilisation of the condylar fracture was achieved with screw fixation in all cases, which was supplemented with additional fixation in three cases. Complications consequent to the surgical intervention occurred in two cases: a femoral fracture and loss of fixation. Three rabbits were reported to have recovered normal limb function, and the rabbit that developed a femoral fracture as a consequence of its surgical intervention was treated with amputation.